Graphene oxide cellular patches for mesenchymal stem cell-based cancer therapy. (April 2018) - Suryaprakash, Smruthi; Li, Mingqiang; Lao, Yeh-Hsing; Wang, Hong-Xia; Leong, Kam W.
Abstract: Graphene oxide (GO) is a versatile platform for drug delivery, but poor accumulation at the tumor site limits the translation of this technology. Mesenchymal stem cells (MSC) on the other hand is tumor trophic but is limited to delivering only protein-based drugs. Our solution is to combine the individual attributes of GO and MSC by loading GO on the surface of MSC to create a unique drug delivery platform wherein, GO can be used to load a range of therapeutics and MSC can carry the drug effectively to the site of the tumor. Here, we demonstrated that GO can be loaded with two types of chemo drugs, doxorubicin and mitoxantrone, with similar efficiency (>30%). The drug-GO complex was loaded on MSC without affecting the MSC viability significantly. On exposure to GO-mitoxantrone, 87% of MSC survived while only 28% of the cancer cells (LN18) survived, demonstrating the selective killing of the cancer cells but not MSC. Furthermore, drug-GO loading did not affect the tumor trophic property of MSC, and co-culture of the drug-GO loaded MSC with LN18 showed a dose-dependent killing of LN18. Together, these results show the feasibility of using drug-GO loaded MSC as an effective carrier for cancer therapy. Graphical abstract: Image 1